Olvido García Valdés’ «The Fall of Icarus». (Re)reading a Myth (Castilla. Estudios de Literatura, 2021)
The aim of the article is to read "The fall of Icarus", a poem by Olvido García Valdés, paying attention to the features which best define its foundational character in her poetics. The poem presents an unusual dialogue with the myth and, specifically, with La chute d'Icare, an anonymous painting traditionally attributed to Pieter Bruegel the Elder. In fact, the point of union between the text and the painting is found, beyond the ekphrasis, in the perspective applied to the myth. For García Valdés, Icarus reveals the perishable human condition and, once assumed, attests to a vital attitude that combines misery with the imperturbable presence of beauty throughout the world.
Keywords: Olvido García Valdés; Icarus; Pieter Bruegel the Elder; Contemporary Spanish Poetry; Painting